Pengaruh Waktu Panen dan Pemberian Pupuk OrganikTerhadap Hasil Tanaman Wortel (Daucus carota L.) - Reni Nurhayatini; Nurdin Hadirochmat (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2015)
A field experiment was conducted to study the effect of harvest time and dosage of organic fertilizer application on the yield of carrot (Daucus carota L.). This research was conducted at the experimental garden plants owned by Faculty of Agriculture, University of Winaya Mukti, in Tanjungsari, Sumedang. The height of this location is 850 meters above sea level with type C precipitation (rather wet). This research was conducted from January 2013 to April 2013.The design used in this research was a randomized block design (RBD) with factorial pattern consisting of two treatment factors i.e. the time of harvest (W) and organic fertilizers dosage (P) which were repeated 2 times. The first factor (W) consistedof four levels i.e. (w1) = 90 HST, (w2) = 100 HST, (w3) = 110 hst, and (w4) = 120 HST. The second factor (P) consists of four levels which are (p0) = 0 tonnes haˉ¹, (p1) = 10 tons haˉ¹, (p2) = 20 tons haˉ¹,and (p3) = 30 tons haˉ¹.This experiment showed that there is no interaction between the application of thechicken coop organic fertilizer dosage with the harvest of the crops of carrot. However, treatment given to the 20 tons haˉ¹ dose of chicken coop organic fertilizer affected the weight of fresh roots, long tubers, the diameter of the bulbs, and the levels of vitamin C. Because the required application of the fertilizer will show the weight of fresh tubers larger, long tubers longer, heavier bulb diameter, and showed an increase in levels of vitamin C.Treatment of HST 100 time harvest affected the fresh tuber weight and the content of vitamin C, because this treatment is as needed; which then will show a heavier bulb diameter, as well as elevated levels of vitamin C.